Multiple stage tissue expansion for reconstruction of scalp nevocellular nevus in pediatric age group - AlBurshaid, Hiba (GMS Interdiscip Plast Reconstr Surg DGPW, 2019)
Aim: To present a rare case of giant congenital nevocellular nevus in a 7-year-old girl’s scalp and to highlight our management steps and outcomes. Case description: An otherwise healthy 7-year-old girl presented to plastic surgery clinic with a giant congenital nevus (GCN) that covered almost her entire scalp that was treated successfully with tissue expander three times over a period of 14 months. A total of 34 cm width of skin, which comprised 78% of the patient’s scalp, was removed. The patient was reassessed five years later with a great cosmetic outcome represented by a remarkable hair growth and near normal scalp appearance. Conclusion: Giant scalp nevocellular nevi in pediatric age group can be treated completely with tissue expanders more than twice to achieve near normal outcomes.